2018
DOI: 10.1111/codi.13839
|View full text |Cite
|
Sign up to set email alerts
|

Social media use in German visceral surgeons: a cross‐sectional study of a national cohort

Abstract: German visceral surgeons are less engaged and less active on social media than previously examined cohorts. Loco-regional, cultural, demographic and regulatory matters may have a significant influence on uptake. If this surgical cohort wishes to have a wider international presence then education on the potential benefits of these tools may be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
2
7
0
1
Order By: Relevance
“…This is consistent with a similar study on hernia surgical specialists in 2016 [21]. While there seems to be a geographical difference in the popularity of SM, especially in Europe and North America, we recently found that rates were much lower in German colorectal surgeons (3.8% Twitter, 24% Lin-kedIn) [7]. This effect may be either cultural or due to the English language, where there may be a greater attraction for English speakers to engage with already popular SM tools, such as hashtags for access to up-to-date educational resources.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with a similar study on hernia surgical specialists in 2016 [21]. While there seems to be a geographical difference in the popularity of SM, especially in Europe and North America, we recently found that rates were much lower in German colorectal surgeons (3.8% Twitter, 24% Lin-kedIn) [7]. This effect may be either cultural or due to the English language, where there may be a greater attraction for English speakers to engage with already popular SM tools, such as hashtags for access to up-to-date educational resources.…”
Section: Discussionsupporting
confidence: 92%
“…There may also be local factors limiting the use of SM (e.g. ease of access, regulatory matters, government censorship) [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of previous, broader studies regarding social media and citation [13,18,38,39]. Studies have further found that colorectal surgeons tend to be weakly engaged with social media [22,23] and that, although the uptake of social media is steadily increasing, a large geographical variation still persists [40]. These findings suggest that the important role of social media in the communication of medical information has yet to be fully appreciated, despite papers demonstrating the value of social media in conducting and promoting research in the field of coloproctology [41,42] and even those suggesting the relatively active use of social media by colorectal surgeons [43].…”
Section: Resultssupporting
confidence: 92%
“…Critically, not all such studies showed a significant correlation between the two variables; therefore, this topic remains somewhat controversial [20,21]. The controversy is further underlined by the fact that only about 28% of medical journals had Twitter profiles in 2015 [10] and this finding could explain the relatively low engagement of colorectal surgeons with social media [22,23]. To further clarify this issue, this study aimed to elucidate the impact of Twitter on citation rates by performing a bibliometric analysis of articles selected from three coloproctology journals which do engage readership through the platform.…”
Section: Introductionmentioning
confidence: 99%